Roland Barthes' Semiotic Analysis of the Representation of Social Criticism on the Instagram Account @Freakind.Media - Syaiful Halim; Hadi Anwar Mutha (Journal of Sustainable Community Development, 2023)
The development of social media has transformed public communication patterns and created new spaces for individuals to express opinions, share perspectives, and deliver social criticism regarding various social, political, and economic issues. Instagram has emerged as one of the most influential platforms for communicating social criticism through creative and widely accessible visual content. One account that consistently produces critical content is the Instagram account @freakind.media. This study aims to analyze the representation of social criticism in the content published by @freakind.media using Roland Barthes’ semiotic approach. Employing a qualitative research method, data were collected through observation and documentation of selected Instagram posts published between April 1 and April 25, 2025. The analysis was conducted using Barthes’ three levels of meaning: denotation, connotation, and myth. The findings reveal that the content of @freakind.media utilizes visual signs, symbols, illustrations, and satirical narratives to represent criticism of contemporary social, political, and economic issues. At the denotative level, the posts depict actual events and public phenomena. At the connotative level, visual elements construct meanings associated with criticism, satire, and resistance toward social inequalities. At the mythological level, the content reproduces broader understandings of power relations, social injustice, and the role of citizens in monitoring public policies. This study demonstrates that Instagram functions not only as a platform for entertainment and information sharing but also as a space for meaning production and the articulation of social criticism within the digital communication environment.